Studies of the sintering method of ash and slag waste for the production of alumina from self-disintegrating sinters - Altynsary Bakirov; Ablay Zhunusov; Natalya Oleinikova; Raigul Ramazanova (Heliyon)
The goal of this research is to select the optimal composition of the sintering charge of ash and slag waste for maximum extraction of alumina and obtaining self-disintegrating sinters of a given chemical composition. Experiments have shown that sintering of ash and slag waste using two-component charges makes it possible to extract alumina from sinters by no more than 60 %. The highest sintering rates were made using three-component charges. So, when sintering ash and slag waste from Almaty TPP-2 on a three-component charge of the composition CaO:SiO2 = 2; Na2O:(Al2O3+Fe2O3) = 1 at a duration of 60 min and a temperature of 1200 °C, alumina extraction was 83.68 %, under the same conditions, alumina extraction of 87.07 % was obtained during sintering of ash and slag waste from the Eurasian Energy Corporation, and alumina extraction was 90.2 % during sintering of ash and slag waste obtained after preliminary chemical activation.As a result of the conducted research on sintering of ash and slag waste in a three–component charge system, a self-disintegrating sinter of the following chemical composition was obtained, %: Na2O – 0.07; CaO – 26.88; SiO2 – 2.06; Fe2O3 – 5.01; Al2O3– 5.059.